ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PERUSAHAAN - RIZKY MIKI UTARI; NURITA AFFAN; BRAMANTIKA OKTAVIANTI (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This research was aimed to analyze the impact of the disclosure of corporate social responsibility to corporate profitability at oil palm plantation company listed in Indonesia Stock Exchange (IDX). In this research, profitability measured was surveyed by used Return On Asset (ROA), Return On Equity (ROE), Return On Investment (ROI), Net Profit Margin (NPM), dan Earning Per Share (EPS).  This research samples used 8 oil palm plantation companies listed in Indonesia Stock Exchange (IDX) year 2010-2014. The data was used annual report or years report that were taken in website www.idx.co.id. The sampling technique was purposive sampling method. The analysis method was a simple regression. The results of this research that disclosure of corporate social responsibility had positive significant impact to ROA, NPM and EPS. But, disclosure of corporate social responsibility did not had impact significant to ROE and ROI.Keywords:   Corporate Social Responsibility (CSR), Profitability, Return On Asset (ROA), Return On Equity (ROE), Return On Investment (ROI), Net Profit Margin (NPM), Earning Per Share (EPS)